Multiband monopole antenna for mobile applications - Saravanan, S. S.; Majid, H. A.; Esmail, B.A.F; Fadhali, N.; Abidin, Z.Z.; Shah, S.M.; Rahim, M.K.A. (2019)
— In this paper, a multiband monopole antenna has been proposed for mobile applications. The monopole antenna has simple structure with a physical size of 15 cm × 7 cm. The antenna consists of monopole shape loaded by a set of folded arms with a varying length which lead to a better impedance matching result and multiband performance. The simulated results show that the proposed antenna provide multiband frequency operation of 0.8 GHz, 1.8 GHz 2.1 GHz, 2.6 GHz and 3.5 GHz which covers the range from 0 to 4 GHz. The antenna is designed to operate at sub-6 GHz which proposed as lower frequency band to deliver 5G in early stage. The designed antenna has been fabricated and measured to validate the simulated results. RF Coaxial U.FL Connector was used as the port connector. The measurement results agrees well with the simulated ones for all frequency bands.